Pengembangan Modular Smart PJU di Gang Makam dan Terminal Keputih Surabaya - Bayu Sandi Marta; Fernando Ardilla; Iwan Kurnianto Wibowo; Dewi Mutiara Sari; Dwi Kurnia Basuki; Mochamad Mobed Bachtiar; Eko Susanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Street lighting (PJU) is a crucial infrastructure for supporting public safety and mobility, particularly in the Gang Makam Keputih area and around the Keputih Terminal in Surabaya. In 2025, the PENS Computer Engineering Study Program implemented community service through the development of an Internet of Things (IoT)-based Smart Street Lighting (Street Lighting) system with a simpler and more accurate architecture than previous systems. The system utilizes a single ESP32 microcontroller integrated with a PZEM energy measurement module and a Real Time Clock (RTC) to read voltage, current, power, energy, and power factor parameters in real time and send data to a server via WiFi for display on a web-based monitoring dashboard. Implementation results demonstrated stable system performance and improved effectiveness of remote monitoring and control, with an average user satisfaction rating of 8.7/10 for device usability and 8.6/10 for website usability. Therefore, this system is considered worthy of development and replication in other areas.